The Influence Of School-Based Continuing Professional Development On The Implementation Of The Competency-Based Curriculum In Mathematics Education In Selected Secondary Schools Of Katete District, Eastern Province, Zambia (Journal of Education and Physical Studies, 2026)
The impact of School Based Continuing Professional Development (SBCPD) on the implementation of Competency Based Curriculum (CBC) in Mathematics Education in selected secondary schools of Katete District, Eastern Province, Zambia was investigated. The research used a qualitative research design, and secondary data was gathered from peer-reviewed academic articles, government education policy documents, curriculum frameworks and previous empirical studies to explore how the role of the SBCPD influences teachers' pedagogical competencies, teaching and learning practices, and assessment practices in the context of CBC. The theoretical framework of the study was guided by three theories, namely Vygotsky's Social Constructivist Theory, Knowles' Andragogy Theory, and Mezirow's Transformative Learning. Secondary data were analysed systematically using thematic analysis as described by Braun and Clarke (2006) and with six phases. Results indicated that the sustained SBCPD had a significant impact on teachers' implementation of pedagogies that are learner-centred, competency-based assessment practices, and collaborative lesson planning. However, serious issues like lack of government support, insufficient teaching materials or too many tasks for teachers, poor administrative supervision and so on remained a key barrier. The study adds to the scholarly discourse on curriculum reform and teacher professional development in countries of sub-Saharan Africa, providing the evidence-based recommendations for enhancing SBCPD to speed up the processes of CBC implementation in Eastern Province secondary schools.
Keywords: Curriculum, Competence, Institutionalisation, collaborative and Implementation